The Cassava Wastewater Treatment System with and without Recirculation – Challenge and Prospect - Eganoosi Atojunere (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
The volume of wastewater produced during the secondary processing of cassava into cassava products is significant. This growing concern is not intended to undermine the importance of cassava as a staple food in many countries; instead, it is linked to the way wastewater is handled, which is considered deficient. This review is based on secondary data gathered from over 50 studies published between 2005 and 2025 on different treatment methods for cassava wastewater. It compared the Removal Efficiency (RE) of two existing Cassava Wastewater Treatment Systems: one with Recirculation (CWTS-R) and the other without Recirculation (CWTS-WR). The REs were based on four studied physicochemical parameters: Suspended Solids (SS), COD, turbidity, and cyanide. The trend for the REs was: pH 56 > 33.4; SS 45 > 42.3; COD 47 > 43.2; Turbidity 56 > 25.2; and Cyanide 40 > 38.3 for CWTS-R and CWTS-WR. The data obtained revealed that the REs for the CWTS-R were higher across all studied physiochemical parameters than those for the CWTS-WR. The contaminants removal abilities of the CWTS-R and CWTS-WR were significantly different. The increase in the REs might not be unrelated to the addition of a pump that redirects cassava wastewater back to the starting treatment points when the set threshold limits for these parameters are exceeded. Optimizing the operations of the existing CWTS-R and CWTS-WR is recommended to improve efficiency.